Automatic individual Weapon Detection System to Increase Security for Police Officers to Recognizing Terrorists - Parlindungan, (International Journal of Psychosocial Rehabilitation, 2020)
an attack with a firearm becomes a serious threat to a security and a threat to a nation and state, where now a firearm is very easy to find and use so that regulations are needed to use it especially if the weapon falls on the wrong person and attack crimes using firearms continue to increase. These crime targets are not only personal but are carried out in groups and planned, in some developed countries attacks using firearms are able to be identified 40 minutes after the first gun explosion and the police or security officers will provide a quick response, but The problem currently faced is that security officers are late in identifying criminals because of the type of attack carried out in secret and in terms of unpredictable time, attacks with firearms will target important objects such as malls, airports, oil refinery and other facilities, the solution to this problem is to carry out a rapid identification process before the attack occurs, the identification system can be done with the help of a computer camera or CCTV installed in a public place, the camera will identify a threat seen from the main characteristics for example weapon objects appear in misplaced vital objects then the system identifies the weapon carrier including security officers or not because it often happens officers and terrorists will use the same type of weapon, the computer system will automatically give a visual appearance and categorize the object as a threat or not, This identification system has an accuracy value between 80-90% in analyzing and identifying weapon objects